Recollection and new data on the distribution of Aeschynanthus elmeri (Gesneriaceae) from the island of Mindanao, Southern Philippines - Naive, Mark Arcebal K. (Phytotaxa, 2023)
Recent fieldwork within Zamboanga peninsula revealed the recollection of the poorly known Philippine endemic Gesneriaceae species, Aeschynanthus elmeri. The name is herein lectotypified and a detailed description based on our recent collections, comparison to its closely similar species, ecology, updated geographical distribution information and a provisional IUCN conservation assessment is provided below.